Bienestar social y la autoestima de un adulto con discapacidad intelectual - Sánchez Cacay, Jean Pierre (Machala: Universidad Técnica de Machala, 2024)
Social well-being and self-esteem are essential for improving the quality of life in adults with intellectual disabilities. Social well-being helps regenerate positive interpersonal relationships and fosters a sense of belonging and support within a community. On the other hand, self-esteem is the evaluation and acceptance of oneself, which is crucial for self-confidence and personal motivation. This case study focuses on an adult diagnosed with an intellectual disability ID, leading to the following research question: ¿What is the relationship between social well-being and self-esteem in an adult with an intellectual disability? The main objective of the research is described as follows: To analyze the existing relationship between social well-being and self-esteem in an adult with an intellectual disability. A qualitative paradigm was applied, followed by a descriptive research type. Data collection instruments included an interview with the family, a questionnaire to determine social well-being, and a self-esteem test. These tools revealed that the individual's self-esteem is low in several dimensions, such as personal selfawareness, security, self-confidence, communication skills, and social perception. All these dimensions negatively affect the self-esteem of the adult with an intellectual disability. Moreover, social well-being is at a moderate level, with observations showing that the person receives significant support in various important aspects of their life, thanks to regular visits from friends and family who provide an adequate amount of love and affection. Both variables are fundamental for enhancing the emotional and psychological development of a person, especially in adults with intellectual disabilities. By fostering good social integration and positive self-esteem, their quality of life can continue to improve.
El bienestar social y la autoestima son primordiales para mejorar la calidad de vida en personas adultas con discapacidad intelectual. El bienestar social proporciona regenerar las relaciones interpersonales positivas y sentirse parte de una comunidad, lo cual desarrolla un sentido de pertinencia y apoyo. Por otro lado, la autoestima es una valoración y aceptación de uno mismo, muy fundamental para la autoconfianza y la motivación personal, de manera que se aborda el siguiente estudio de caso enfocado en un adulto diagnosticado con discapacidad intelectual DI, a partir de esto surge la siguiente pregunta problema. Qué relación existe entre el bienestar social y la autoestima de un adulto con discapacidad intelectual. Para esto se describe como objetivo principal de la investigación lo siguiente. Analizar la relación existente entre el bienestar social y la autoestima de un adulto con discapacidad intelectual. Así mismo, el paradigma aplicado fue el cualitativo, seguido de un tipo de investigación descriptiva. De igual modo, fueron aplicados como instrumentos de recolección de datos: una entrevista a los padres de familia, un cuestionario para determinar el bienestar social y un test de auto estimación, estas herramientas permitieron conocer su autoestima, que está en un nivel bajo en varias dimensiones como: el autoconocimiento personal, seguridad, confianza en sí mismo, habilidades de comunicación y la percepción social. Todas estas dimensiones perjudican la autoestima del adulto con discapacidad intelectual. Además, el bienestar social está en un nivel moderado, donde se observó que la persona recibe mucho apoyo en varios aspectos importantes de su vida, gracias a las visitas constantes de amigos y familiares que le brindan una cantidad adecuada de amor y afecto. Ambas variables son fundamentales para mejorar el desarrollo emocional y psicológico de una persona, especialmente en adultos con discapacidad intelectual, donde al generar una buena
Keywords: BIENESTAR SOCIAL; AUTOESTIMA; ADULTO; DISCAPACIDAD INTELECTUAL